Circadian Rhythm Disruption Presenting as Adrenal Insufficiency: Diagnostic Challenges and Clinical Implications - Alshamsi, Shamma; Afandi, Bachar (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
We describe the case of a 24-year-old woman with persistently low early morning cortisol levels and an initial adrenocorticotropic hormone stimulation test demonstrating a preserved cortisol response, raising concern for possible secondary adrenal insufficiency. Pituitary imaging and laboratory evaluation revealed a nonfunctioning pituitary microincidentaloma. Subsequent testing demonstrated higher serum cortisol levels later in the day. Further history revealed a longstanding delayed sleep phase, and serial cortisol testing suggested a shifted diurnal rhythm. This case highlights the importance of interpreting cortisol results in the context of clinical presentation, behavioral patterns, and circadian timing and raises awareness of the emerging concept of circadian misalignment impacting endocrine evaluation.
Keywords: low morning cortisol; ACTH stimulation test; secondary adrenal insufficiency; pituitary microadenoma; circadian misalignment; HPA axis; hypothalamus pituitary axis